Tumour-associated neutrophils and loss of epithelial PTEN can promote corticosteroid-insensitive MMP-9 expression in the chronically inflamed lung microenvironment - Vannitamby, Amanda (Thorax, 2017)
Matrix metalloproteinase-9 (MMP-9) is increased in a number of pathological lung conditions, where the proteinase contributes to deleterious remodelling of the airways. While both lung cancer and COPD are associated with increased MMP-9 expression, the cellular and molecular drivers of MMP-9 remain unresolved. In this study, MMP-9 transcript measured within the tumour region from patients with non-small-cell lung cancer (NSCLC) and coexisting COPD was found to be uniformly increased relative to adjacent tumour-free tissue. MMP-9 gene expression and immunohistochemistry identified tumour-associated neutrophils, but not macrophages, as a predominant source of this proteinase. In addition, PTEN gene expression was significantly reduced in tumour and there was evidence of epithelial MMP-9 expression. To explore whether PTEN can regulate epithelial MMP-9 expression, a small interfering (si)RNA knockdown strategy was used in Beas-2B bronchial epithelial cells. PTEN knockdown by siRNA selectively increased MMP-9 expression in response to lipopolysaccharide in a corticosteroid-insensitive manner. In summary, tumour-associated neutrophils represent an important source of MMP-9 in NSCLC, and loss of epithelial PTEN may further augment steroid-insensitive expression.